Results from the German registry for refractory celiac disease - Weber, Marko; Wolf, Nina; Branchi, Federica; Tangermann, Paul; Itzlinger, Alice; Poralla, Lukas; Preiß, Jan C.; Grunert, Philip; Daum, Severin; Siegmund, Britta; Stallmach, Andreas; Schumann, Michael (Zeitschrift für Gastroenterologie, 2021)
Refractory celiac disease (RCD) refers to a rare subgroup of patients with celiac disease who show clinical signs of malabsorption despite a gluten-free diet. RCD is divided into an autoimmune phenotype (RCD type I) and pre-lymphoma (RCD type II). To reflect the clinical reality in managing this disease in Germany, a national register was established based on a questionnaire developed specifically for this purpose. Between 2014 and 2020, a total of 53 patients were registered. The diagnosis of RCD was confirmed in 46 cases (87%). This included 27 patients (59%) with RCD type I and 19 patients (41%) with RCD type II. A wide range of diagnostic and therapeutic measures was used. Therapeutically, budesonide was used in 59% of the RCD patients regardless of the subtype. Nutritional therapy was used in only 5 patients (11%). Overall mortality was 26% (12 patients) with a clear dominance in patients with RCD type II (9 patients, 47%). In summary, RCD needs to become a focus of national guidelines to increase awareness, establish standards, and thus enable the treating physician to make the correct diagnosis in a timely manner. Moreover, we concluded that when treating such patients, contacting a specialized center is recommended to ensure sufficient management.
Keywords: Zöliakie; Refraktäre Zöliakie; Register; T-Zell Lymphom; ulzerative Jejunitis